[The Horse Racing Track, The Queen’s Park Savannah, Port of Spain, Trinidad] - (:unkn) unknown (My University, 2010)
This old photograph shows the horse racing track at the Queen’s Park Savannah, Port of Spain. The track winds around the Savannah’s large trees and animals appear to be grazing among them. A section of the Northern Range is visible in the background. The first horse race recorded to have taken place here was in 1828 and horse racing continued at the savannah until 1994.
Colour: Black and White; Style: Landscape; Other: Bordered; Undivided
Keywords: Trinidad and Tobago; Postcards; Horse racing--Trinidad and Tobago; Savannas--Trinidad and Tobago; Trees--Trinidad and Tobago; Mountains--Trinidad and Tobago; Racetracks (Horse racing)--Trinidad and Tobago; Queen's Park Savannah